2006
DOI: 10.1007/s11136-006-0003-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life as a potential predictor for morbidity and mortality in patients with metastatic hormone-refractory prostate cancer

Abstract: Patients with better baseline HRQL have better predicted survival, time to disease progression and pain prognosis than those with worse HRQL. In addition, the 12-week change in HRQL appears to improve predictive accuracy for most clinical outcomes. It appears that greater deterioration in HRQL is prognostic for rapid disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 39 publications
1
59
0
1
Order By: Relevance
“…45,47 In this context, Oliva et al reported a study on elderly AML patients in which QOL physical functioning was of prognostic relevance yet, somewhat surprisingly, did not correlate to the physician-assessed ECOG performance status. 48 While the item 'fatigue' has been shown to be prognostically relevant in several different malignant diseases, 47,[49][50][51] so far only hypotheses to explain the mechanisms underlying the association between reported data on patient health status and duration of survival have been proposed. 52 'Fatigue' is a patient-reported outcome and multi-faceted concept including both mental and physical components whose critical domains have not been sufficiently standardized and for which several scales have been developed.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…45,47 In this context, Oliva et al reported a study on elderly AML patients in which QOL physical functioning was of prognostic relevance yet, somewhat surprisingly, did not correlate to the physician-assessed ECOG performance status. 48 While the item 'fatigue' has been shown to be prognostically relevant in several different malignant diseases, 47,[49][50][51] so far only hypotheses to explain the mechanisms underlying the association between reported data on patient health status and duration of survival have been proposed. 52 'Fatigue' is a patient-reported outcome and multi-faceted concept including both mental and physical components whose critical domains have not been sufficiently standardized and for which several scales have been developed.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…Baseline global QOL was a strong independent predictor of survival in patients with advanced CRC in one study [Maisey et al 2002], while in another study, the patient's score on the social functioning scale translated into a 9% decrease in the patient's hazard of death for any 10-point increase in the score (0 to 100 scale) [Efficace et al 2008[Efficace et al , 2006a. A correlation between various pretreatment PRO domain scores, including overall quality of life [Qi et al 2009], global quality of life [Movsas et al 2009 [Roychowdhury et al 2003] and total quality of life score in metastatic HRPC [Sullivan et al 2006] and in localized prostate cancer [Sadetsky et al 2009] have been associated with survival.…”
Section: Prediction and Prognosismentioning
confidence: 99%
“…The association between baseline QoL and survival in prostate cancer has been investigated and reported in a few previously published studies [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline or pretreatment QoL has been shown to be a prognostic indicator in prostate cancer in previously published studies [10][11][12][13]. However, to the best of our knowledge, there is no study in the literature investigating the prognostic impact of changes in QoL scores on survival in prostate cancer, whether this is assessed at the time of initial cancer diagnosis or following disease relapse.…”
Section: Introductionmentioning
confidence: 99%